Molecular construct of Mutant Carbohydrate-Binding Domain (CBM40) from Vibrio cholerae Non-O1 Sialidase - Nadiawati, Alias; Noor Asidah, Mohamed; Gogula Selvi, Asang (2021)
Carbohydrate-Binding Module Family 40 (CBM40) is known as a carbohydrate-binding domain which recognizes sialic acid as a substrate. CBM functions to concentrate the enzyme in proximity close to the substrate for efficient hydrolysis. The elimination of this CBM from most protein domains often leads to declined enzyme activity and efficiency. Gene encoding for family 40 CBM from Vibrio cholerae Non-O1 sialidase was cloned and successfully expressed in E. coli BL21 (DE3) strain. The CBM40 encoded 195 amino acids with 585 bp of nucleotide sequence. In the present study, CBM40 was genetically modified by site-directed mutagenesis to form a stable CBM40 domain with a better substrate-binding affinity towards sialic acid. With the intention to evaluate the impact of single mutagenesis of the CBM40 residue on substrate binding affinity, in silico analysis was carried out using UCSF Chimera. Mutation of Thr200 to Asn200 was successfully performed using the Quik Change II Site-Directed Mutagenesis Kit (Agilent). The results gained by in silico analysis revealed that the affinity of mutant CBM40 was higher than wild type CBM40 due to increases of three hydrogen binding sites with sialic acid.